Comparison of Fine Needle Aspiration and Fine Needle Nonaspiration Cytology of Thyroid Nodules: A Meta-Analysis. (29th September 2015) - Song, Hongming; Wei, Chuankui; Li, Dengfeng; Hua, Kaiyao; Song, Jialu; Maskey, Niraj; Fang, Lin
Abstract : Background . Fine needle aspiration cytology (FNAC) and fine needle nonaspiration cytology (FNNAC) are useful cost-effective techniques for preoperatively assessing thyroid lesions. Both techniques have advantages and disadvantages, and there is controversy over which method is superior. This meta-analysis was performed to evaluate the differences between FNAC and FNNAC for diagnosis of thyroid nodules. Methods . Primary publications were independently collected by two reviewers from PubMed, Web of Science, Google Scholar, EBSCO, OALib, and the Cochrane Library databases. The following search terms were used: fine needle, aspiration, capillary, nonaspiration, sampling without aspiration, thyroid, and cytology. The last search was performed on February 1, 2015. Results . Sixteen studies comprising 1, 842 patients and 2, 221 samples were included in this study. No statistically significant difference was observed between FNAC and FNNAC groups with respect to diagnostically inadequate smears, diagnostically superior smears, diagnostic performance (accuracy, sensitivity, specificity, negative predictive value, and positive predictive value), area under the summary receiver operating characteristic curve, average score of each parameter (background blood or clot, amount of cellular material, degree of cellular degeneration, degree of cellular trauma, and retention of appropriate architecture), and total score of five parameters. Conclusion . FNAC and FNNAC are equally useful in assessing thyroid nodules.